Activation of Cholinergic Anti-Inflammatory Pathway Ameliorates Cerebral and Cardiac Dysfunction After Intracerebral Hemorrhage Through Autophagy - Su, Yue; Zhang, Wei; Zhang, Ruoxi; Yuan, Quan; Wu, Ruixia; Liu, Xiaoxuan; Wuri, Jimusi; Li, Ran; Yan, Tao (Frontiers in Immunology, 2022)
Intracerebral hemorrhage is the most devastating stroke subtype with cardiovascular complications resulting to high rates of mortality and morbidity with the release of inflammatory factors. Previous studies have shown that activation of α7nAChR can alleviate inflammation and immune related diseases by triggering the cholinergic anti-inflammatory pathway. α7nAChR-mediated protective roles against neuroinflammation via AMPK–mTOR– p70S6K related autophagy. Therefore, the aim of our experiment is to explore whether the activation of α7nAChR improved the cerebral and cardiac dysfunction after ICH through autophagy. Male C57 mice were subjected to ICH and randomly treated with: (1) Sham + saline, (2) ICH+ saline, (3) ICH + PNU-282987, (4) ICH+ PNU-282987 + MLA, (5) ICH + PNU-282987 + 3-MA. The neurological function were evaluated at multiple time points. Brain water content were measured on 3 days to assess brain edema. PCR, immunofluorescence staining and Western Blot were performed on 7 days to evaluate inflammation and autophagy. PSR were measured on 30 days to evaluate myocardial fibrosis, echocardiography were performed on 3 and 30 days to measure cardiac function. Our results indicated that activation of α7nAChR reduced inflammatory factors (MCP-1, IL-1β, MMP-9, TNF-α, HMGB1, TLR2), promoted the polarization of macrophages/microglia into anti-inflammatory subtypes(CD206), repaired blood-brain barrier injury(ZO-1, Claudin-5, Occludin),alleviated acute brain edema and then recovered neurological dysfunction. Echocardiography and PSR indicated that activation of α7nAChR ameliorated cardiac dysfunction. Western Blot showed that autophagy protein (LC3, Beclin) was increased and P62 was decreased. It demonstrated that the activation of α7nAChR promotes autophagy and then recovers brain and heart function after ICH. In conclusion, activation of α7nAChR improved the cerebral and cardiac dysfunction after ICH through autophagy.